2017
DOI: 10.1007/s10701-017-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Tests and Problems of the Standard Model in Cosmology

Abstract: The main foundations of the standard ΛCDM model of cosmology are that: 1) The redshifts of the galaxies are due to the expansion of the Universe plus peculiar motions; 2) The cosmic microwave background radiation and its anisotropies derive from the high energy primordial Universe when matter and radiation became decoupled; 3) The abundance pattern of the light elements is explained in terms of primordial nucleosynthesis; and 4) The formation and evolution of galaxies can be explained only in terms of gravitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 395 publications
(452 reference statements)
0
73
0
Order By: Relevance
“…This finding is considered by many cosmologist, including López-Corredoira [4] and Orlov and Raikov [5], as inconsistent with other findings, and by Crawford [13], as flawed. Hawkins [14] did not find any time dilation in 878 quasars.…”
Section: Analysis Using Observational μ Z Databasementioning
confidence: 86%
See 1 more Smart Citation
“…This finding is considered by many cosmologist, including López-Corredoira [4] and Orlov and Raikov [5], as inconsistent with other findings, and by Crawford [13], as flawed. Hawkins [14] did not find any time dilation in 878 quasars.…”
Section: Analysis Using Observational μ Z Databasementioning
confidence: 86%
“…The status of the expanding universe and steady state theories has been recently reviewed by López-Corredoira [4] and Orlov and Raikov [5]. They concluded that based on the currently available observational data it is not possible to unambiguously identify the preferred approach to cosmology.…”
Section: Introductionmentioning
confidence: 99%
“…Actual Dark Matter particle searches at the "Conseil Européen pour la Recherche Nucléaire" Large Hadron Collider (CERN LHC) were reviewed by Kahlhoefer [7]. The Standard Cosmological Model which predicts the relative percentage of Dark Matter in the universe was recently critically reviewed in [8]. Reviews of Dark Matter can be found in [9] and [10].…”
Section: Introductionmentioning
confidence: 99%
“…The geometry for the CNO's center to distances from the center of the galaxies was used for computing the density differences for: (a) the canted Milky Way's center to 8 kilo parsecs out from the center using the law of cosines; (b) the simpler geometry for M31 from the center to 15 kilo parsecs out with no cant angle. The virial velocity contribution from the CNO was determined using Equation (7), where the mass at the location from the center (R 1 ) and the mass at the center (R C ) were computed by integrating our degenerate neutrino density solutions for various potential degenerate neutrino masses with CNO central Fermi momentum boundary conditions from the CNO center in Equation (8) out to these specific (R 1 and R C ) distances 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation